2003
DOI: 10.15298/arctoa.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Systematic position of Habrodon (Habrodontaceae, Musci) as inferred from nuclear ITS1 and ITS2 and chloroplast trnL intron and trnL–trnF spacer sequence data

Abstract: Systematic position of the genus Habrodon was considered quite differently by various authors it was placed in Habrodontaceae, Fabroniaceae, Myriniaceae, Leskeaceae, and Pterigynandraceae. The analysis of nucleotide sequence data (chloroplast trnL-F region and nuclear ITS1 & ITS2) was undertaken to elucidate Habrodon relationshi ps. This analysis revealed quite distinct position of Habrodon from Leskea and Myrinia, and found Habrodon within a paraphyletic grade with Plagiotheciaceae (sensu lato, cf. Hedenäs, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…BASAL HYPNALES Previous studies on the Habrodontaceae (Budyakova et al, 2003) and current observations on Acrocaldium, (Figs. 45-50 (Fig.…”
Section: -46mentioning
confidence: 79%
See 2 more Smart Citations
“…BASAL HYPNALES Previous studies on the Habrodontaceae (Budyakova et al, 2003) and current observations on Acrocaldium, (Figs. 45-50 (Fig.…”
Section: -46mentioning
confidence: 79%
“…In order to avoid misleading terminology, we suggest that cases sometimes described as "pseudoparaphyllia absent or present" (Budyakova et al, 2003) refer to the Bryumand Climacium-types of branch primordia developed by Akiyama (1990) and Akiyama & Nishimura (1993) based on the original distinction of these types by Lorch (1931). Accepting this, we suggest a slightly different terminology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th erefore, Buck and Crum (1990) put these fi ve genera into the family Pterigynandraceae. Although this classifi cation was accepted later by Buck and Goffinet (2000) and Goffinet and Buck (2004), the analysis of nucleotide sequence data suggested that Pterigynandraceae sensu Buck and Crum (1990) is not monophyletic (Budyakova et al 2003). According to Newton and Tangney (2007) the correct phylogenetic position of the genus Heterocladium is certainly out of Pterigynandraceae.…”
Section: Introductionmentioning
confidence: 99%
“…The confusing habit forced us to check the systematic position of the latter species with molecular phylogenetic methods, which in many cases already solved long-standing problems of systematic placements of moss genera. The results of the molecular phylogenetic studies have rectified familial placements of Anacamptodon (Vanderpoorten et al, 2002), Clasmatodon (Buck et al, 2000), Struckia (Pedersen & Hedenäs, 2002), Sasaokaea (Ignatov & Milyutina, 2010), Bissetia, Homaliadelphus and Miyabea ), Lecuraea and Pylaisia (Gardiner et al, 2005), Habrodon (Budyakova et al, 2003), Acrocladium (Tangney et al, 2010) and at least a few tens of other moss genera.…”
Section: Introductionmentioning
confidence: 99%